APPROACH OF THE SITUATION OF THE VENEZUELAN STATE FROM THE CONCEPT OF FAILED STATE - Gonzalez Perez, Petrick Jeanny (2019)
In Internationa Law emerged the notion of the failed state, to name the political and legal system with non-compliance in their role of government, to give way to anarchy and violence. For some authors, specialized in the subject describes as States incapable of maintaining a natural relationship and diplomacy with the international community, which put a risk not only their internal security, but also security of other States. Defining “The State” is to fall into and ambivalence, characterized by ambiguity, many theoretical terms do not end up accepting a solid position on its definition, are directly related to the characteristics or indicators, which ultimately is not safe. For this investigation, the fault lies in the inability of the system to ensure legal security for citizens, human rights and quality of life service. Therefore, an approximation is sought between the concept of a failed state and the real situation in Venezuela, with the perspective of the pertinent measures that can be evidence in the presence of elements of a state that does not fulfill its fundamental role, exploring the indices of the disturbance of the political system called republic.